2019
DOI: 10.3389/fmars.2019.00518
|View full text |Cite
|
Sign up to set email alerts
|

Wind Intensity Is Key to Phytoplankton Spring Bloom Under Climate Change

Abstract: The onset of the spring bloom (OSB) occurs when phytoplankton growth exceeds losses and is promoted by a transition from deep convection to a shallow mixing layer concurrent with increasing light intensities in nutrient-enriched waters. We have combined remotely sensed chlorophyll-a data and high-resolution sea-surface winds to quantify and understand high-latitude spring-bloom dynamics and the effect of varying winds. Increasing winds strengthen turbulent mixing and may eventually cause the mixing depth to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…A coarsening of meteorological forcing resolution causes decreased wind stress on the ocean surface. Our results showing an earlier spring phytoplankton bloom under decreased wind stress are unsurprising given the earlier onset of stratification ( Figure 4) and are consistent with the critical turbulence hypothesis of Taylor and Ferrari (2011) and results of Chiswell (2011) and Vikebø et al (2019) who link the timing of the spring bloom to wind-driven processes. The earlier phytoplankton bloom with decreased wind stress matches trends observed in other shallow systems such as in the European Shelf (González Taboada & 10.1029/2019JC015922…”
Section: Impacts Of Wind Stress On Phytoplankton Phenologysupporting
confidence: 89%
See 1 more Smart Citation
“…A coarsening of meteorological forcing resolution causes decreased wind stress on the ocean surface. Our results showing an earlier spring phytoplankton bloom under decreased wind stress are unsurprising given the earlier onset of stratification ( Figure 4) and are consistent with the critical turbulence hypothesis of Taylor and Ferrari (2011) and results of Chiswell (2011) and Vikebø et al (2019) who link the timing of the spring bloom to wind-driven processes. The earlier phytoplankton bloom with decreased wind stress matches trends observed in other shallow systems such as in the European Shelf (González Taboada & 10.1029/2019JC015922…”
Section: Impacts Of Wind Stress On Phytoplankton Phenologysupporting
confidence: 89%
“…Wind and temperature alter the timing of stratification events in spring and autumn and the strength of stratification in summer, in addition to the amount of turbulent kinetic energy present throughout the water column. Chiswell (2011) links the timing of the spring bloom to a reduction in wind-driven surface mixing with wind intensity estimated to explain up to 60% of the interannual variability in the timing of phytoplankton blooms along the Norwegian shelf (Vikebø et al, 2019). Changing wind conditions have also been shown to both advance and delay the onset of spring phytoplankton blooms (Follows & Dutkiewicz, 2002;Ruiz-Castillo et al, 2019;Sharples et al, 2006;Waniek, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…During a survey campaign in 2013 in the North Atlantic, Naustvoll et al (2020) observed that regions with earlier shallowing of ML are related to earlier spring blooms. Using satellite data from 2003 to 2017 along the Norwegian coast, Vikebø et al (2019) found that years with strong winds delay the spring bloom onset. Using a water column model, Opdal et al (2019) suggested that reducing the water transparency could delay the spring bloom onset in the North Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Also, there is a clear delay in the peak of the larger sizeclasses of C. finmarchicus reflecting the time it takes to develop under the various temperature regimes, typically at a minimum around March-April before the seasonal heating starts. The single vertical lines in the panels indicate times of phytoplankton spring bloom as derived from remote sensing data (Vikebø et al, 2019). Generally, these indicate a delay in spring bloom along the coast, but the value far north (SG8) should be considered with care since it is only based on few data points due of the narrow shelf.…”
Section: Temporal C Finmarchicus Abundancementioning
confidence: 99%
“…Newly hatched larvae need sufficient food to cover metabolic costs and energy requirements for growth, which are additionally dependent on ambient temperature and larval size (Folkvord, 2005). The Norwegian continental shelf is a typical spring-bloom system where light conditions and structuring of the water column trigger phytoplankton and zooplankton production (Stenevik et al, 2007;Vikebø et al, 2019). NEA cod larvae and early juveniles are found to mainly feed upon various stages of Calanus finmarchicus from hatching in mid-March to mid-May until after metamorphosis around June (Sundby, 1995).…”
Section: Introductionmentioning
confidence: 99%